Monitoring V2X applications using DevOps and docker - Rufino, João
Vehicular communications are gaining one of the largest share of the automotive IoT market. The combination of the automotive sector with the transportation resulted in the emergence of the concept of connected vehicles. Therefore, motivating new proposals for real-time applications for managing traffic and incident alerts to improve the overall mobility and road safety. The growing demand for new and better solutions lead to two of the biggest challenges faced in IoT - scalability and interoperability. Therefore in this paper, we propose an highly modular and easily distributable architecture built upon DevOps practices and relying on edge computing to enable V2X applications to be easily deployed and monitored in real-time. The architecture was implemented and a vehicular application was divided in small modules to validate the functionalities of the proposed architecture.